Terremoti in Cile. Storia e immaginazione intorno ad un evento apocalittico (Altre Modernità, 2013)
A number of historical sources chronicle the devastating earthquake that shook the country and destroyed Santiago in 1647, during Chile’s colonial period. More than a century after, Heinrich Kleist published Das Erdbeben in Chili (1811), a fictional relation about the same cataclysm that describes the fatal destiny of two lovers. Surviving the disaster, they are lynched in a church by the fanatic faithful because of their irregular union, that would have caused the wrath and the punishment of God. Kleist’s story is cited also in 8. 8: el miedo en el espejo. Una crónica del terremoto en Chile, an eyewitness account from Mexican writer Juan Villoro, who was in Santiago in 2010, when occurred a terrible earthquake that registered 8.8 on the Richter scale. The author not only describes the people’s reactions to event, but also finds in his experience the impetus for considering how someone who escapes death, having seen it up close, can continue to live. In this context uses the Kleist’s text as a springboard for philosophical reflection on man’s destiny. A apocalyptic disaster can have unexpected consequences depending on the time and place, but also by the interpreter of the facts: in the small and isolated environment of colonial Chile, the will to resist giving in to superstition and to struggle to go on living; in Kleist’s story, abandoning comforting illusions about nature and man’s destiny; in Villoro’s account, awareness that we cannot know how and when the end of the world will arrive, but it lies in wait for us.